The impact of the modified budgeting systems (MBS) on performance measurement in Malaysian central government organisations - Karbhari, Yusuf; Mohamad, Muslim Har Sani (2007)
The introduction of the Modified Budgeting System (MBS) as one of the New Public Financial Management (NPFM) tools to bring the efficiency of private sector into Malaysian government organisations had its implication on these organisations' performance measurement systems. Therefore, by obtaining perceptions of the senior managers in the civil services who experienced the reform, this study examines the impact of the Modified Budgeting System (MBS) had on performance measurement practice in Malaysian central government organisations. Specifically, the respondents were asked about the impact of the MBS on improving output based performance measurement, linkage between inputs and outputs, and developing own output measures. This study also examines who are the stakeholders consulted to develop performance measures and the level of importance that civil service’ managers attach to different types of performance indicators covering both financial and non financial indicators. The study found that generally the respondents agreed that the MBS had improved performance measurement in their organisations, and civil service managers attached more importance on customer related measures than efficiency indicators. Despite of these, weaknesses in implementation was mainly related to resistance to change by managers, thus, this might impede the effective development of the performance measures.